Islamic Education Methods in the Book Taṭawwur Mafhûm an-Naẓariyyah al Tarbawiyyah al-Islâmiyyah Karya Mâjid Irsân al-Kailâny - Sutrisno, Sutrisno; Arsyad, Junaidi; Hanum, Azizah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze: (1) the biography of Mâjid Irsân Al-Kailâny, the author of Taṭawwur Mafhûm An-Naẓariyyah Al-Tarbawiyyah Al-Islâmiyyah, (2) the Islamic educational methods found in Taṭawwur Mafhûm An-Naẓariyyah Al-Tarbawiyyah Al-Islâmiyyah, and (3) the relevance of the development of Islamic educational methods in this book to contemporary educational methods today. This research is a qualitative study with a library research approach. The primary data source in this study is Taṭawwur Mafhûm An-Naẓariyyah Al-Tarbawiyyah Al-Islâmiyyah by Mâjid Irsân Al-Kailâny, supported by scholarly books and journals related to the discussion in this research as secondary sources. The data analysis technique used is content analysis. The results of this study indicate that Taṭawwur Mafhûm An-Naẓariyyah Al-Tarbawiyyah Al-Islâmiyyah by Mâjid Irsân Al-Kailâny contains various Islamic educational methods that are highly relevant to the development of contemporary Islamic education. He applies a variety of methods, sometimes using the lecture method, dialogue method, advice method, and discussion method. These methods are used depending on the conditions and circumstances of the learners. The Islamic educational methods in this book have strong relevance to the development of Islamic educational methods in the modern era. The relevance of the development of Islamic educational methods in Taṭawwur Mafhûm An-Naẓariyyah Al-Tarbawiyyah Al-Islâmiyyah to contemporary educational methods remains highly applicable, not only within households but also in classrooms and schools. In general, these methods complement and support each other.